Oral Health Related Quality of Life Following Extraction of Impacted Third Molar: A Prospective Analytical Study (Nepal Journal of Health Sciences, 2025)
Introduction: Surgical extraction of impacted mandibular third molars is among the most frequently performed oral surgical procedures, often associated with postoperative pain, swelling, and functional limitations, adversely affecting patient’s oral health-related quality of life. Although this procedure is widely practiced, limited evidence exists regarding its impact on daily functioning and well-being in the Nepali context.Objective: To assess effect of surgical removal of impacted mandibular third molars on oral health-related quality of life and to examine the influence of age, gender, and surgical difficulty on postoperative recovery.Methods: A prospective analytical study was conducted among 50 patients aged 18-40 years undergoing extraction of partially or completely impacted mandibular third molars. Oral health-related quality of life was measured preoperatively and on postoperative days 1, 3, 5, and 7 using 14-item Oral Health Impact Profile. Surgical difficulty was classified based on clinical and radiographic criteria. Data were analyzed with R statistical software (version 4.0.2), with significance set at p